Association between Obesity and Asthma in Preschool Mexican Children - Francisco Vázquez-Nava; Jaime Morales Romero; Arturo Córdova-Fernandez; Atenógenes H. Saldívar-González; Carlos F. Vázquez-Rodríguez; Maria del C. Barrientos-Gómez; Dolores Lin-Ochoa; Rodríguez Eliza M. Vázquez (The Scientific World Journal)
The elevated prevalence of obesity as well as of asthma in preschool children has prompted investigators to speculate that obesity in childhood might be a causal factor in the development of asthma. The results obtained to date are debatable. We investigated the association between obesity and asthma in 1,160 preschool Mexican children. Diagnosis of asthma was performed using the International Study of Asthma and Allergy in Childhood (ISAAC) questionnaire. The body mass index (BMI) in units of kg/m2 was determined, and children were categorized according to age- and gender-specific criteria, such as normal weight (5th-85th percentile), overweight (ࣙ85th and <95th percentile), and obesity (ࣙ95th percentile). Power test for logistic regression model was calculated. We found no association between overweight (adjusted OR = 1.02; 95% CI = 0.66–1.58), obesity (adjusted OR = 0.94; 95% CI = 0.68–1.30), and wheezing during the last year as determined by logistic regression model adjusted. We did not find an association between overweight, obesity, and asthma-associated hospitalizations. Further longitudinal studies are required to provide a better understanding of the relationship between obesity and asthma in preschool children.